Bambi activity tools more effective than brick blocks in early childhood development: a comparative study - Asy-syifa Maulida Putri; Hernayanti, Munica Rita; Margono, Margono (Jurnal Kesehatan Ibu dan Anak, 2025)
Early childhood is a critical period for cognitive, motor, and social development. While various play-based tools are used to stimulate child development, there is limited evidence comparing the effectiveness of different tools. This study aimed to compare the effectiveness of Bambi Activity Tools and Brick Blocks in enhancing early childhood development, particularly in fine motor, gross motor, language, and social skills. This quasi-experimental study employed a pretest-posttest control group design. A total of 42 children aged 5–6 years were purposively selected from two kindergartens in Sleman Regency, Indonesia. The intervention was conducted over 4 weeks, with sessions held three times per week for 30–45 minutes. Children in the intervention group used Bambi Activity Tools guided by trained teachers, while the control group used Brick Blocks under similar conditions. Developmental progress was measured using the standardized Kuesioner Pra Skrining Perkembangan (KPSP), a validated and reliable instrument assessing four domains of development. Nutritional status was screened based on BMI-for-age, and baseline demographic comparability between groups was assessed. Both groups showed significant improvement in developmental scores after the intervention; however, the mean increase was significantly greater in the Bambi Activity Tools group (mean difference = 0.95; p < 0.001, Wilcoxon test). Post-intervention comparison between groups using the Mann–Whitney U test also revealed a significant difference favoring the Bambi group (p < 0.001). The findings align with prior studies emphasizing the importance of structured, guided play in promoting developmental milestones. The greater effectiveness of Bambi Activity Tools may be attributed to their multimodal design and targeted stimulation. Maternal education, occupation, and child gender were identified as contextual factors that may influence outcomes, although no significant baseline differences were found between groups. Bambi Activity Tools are more effective than Brick Blocks in enhancing early childhood development. These findings support their integration into early childhood education settings. Future research should explore long-term developmental outcomes and scalability in diverse populations.